The relationship between processing speed and remodeling spatial patterns of intrinsic brain activity in the elderly with different sleep duration - Pu, Li; Zou, Yao; Wang, Yan; Lei, Jia-Ling; Zhao, Xiao-Nan; Zeng, Xia; Yan, Guo-Jian (Frontiers in Neuroscience, 2023)
Objective Brain neuroplasticity in which sleep affects the speed of information processing in the elderly population has not been reported. Therefore, this study was conducted to explore the effects of sleep on information processing speed and its central plasticity mechanism in the elderly. Methods A total of 50 individuals aged 60 and older were enrolled in this case control study. All subjects were divided into two groups according to the sleep time: short sleep duration (< 360 min) (6 men and 19 women; mean age: 66.96 ± 4.28 years old), and non-short sleep duration (> 360 min) (13 men and 12 women). Resting-state functional magnetic resonance imaging (rs-fMRI) data were collected, and the amplitude of low frequency fluctuation (ALFF), regional homogeneity (ReHo), and degree centrality (DC) were calculated for each participant. Two-sample t-tests were performed to compare the ALFF, ReHo, and DC maps between the two groups. Then, the relationships among clinical features, fMRI and cognitive function were analyzed using general linear model. Results Short sleep duration group showed significantly increased ALFF value in the bilateral middle frontal gyrus and right insula; significantly increased ReHo value in the left superior parietal gyrus, and decreased ReHo value in the right crebellum; significantly decreased DC value in the left inferior occipital gyrus, left superior parietal gyrus and right cerebellum (p < 0.05, AlphaSim correction). The ALFF value of right insula is significantly associated with symbol digit modalities test (SDMT) score (β = −0.363, p = 0.033). Conclusion Short sleep duration and processing speed are significantly associated with remodeling spatial patterns of intrinsic brain activity in the elderly.